Wood, Andrew y Roberts, Susan (2011). Economic Geography: places, networks and flows - Morente Pacheco, Francisco J. (Documents d’Anàlisi Geogràfica, 2013)
Wood, Andrew y Roberts, Susan (2011) Economic Geography: places, networks and flows Londres: Routledge, 179 p. ISBN 13: 978-0-415-40181-4